2017
DOI: 10.1089/lap.2016.0420
|View full text |Cite
|
Sign up to set email alerts
|

Transanal Endoscopic Microsurgery Combined with Laparoscopic Colectomy for Synchronous Colorectal Tumors: A Word of Caution

Abstract: The combination of TEM with laparoscopic colectomy is feasible and should be kept in mind as an alternative procedure in case of SCRT. However, more strict selection criteria should be considered and the disadvantages should be discussed with the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
1
0
0
Order By: Relevance
“…Morino et al [ 19 ] noted a temporary decrease in post-procedure anal resting pressure, which returned to preoperative values at a mean time of 4 mo ostoperatively. Our study cohort reported no incidence of incontinence, which is consistent with the reports in other literature[ 30 , 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…Morino et al [ 19 ] noted a temporary decrease in post-procedure anal resting pressure, which returned to preoperative values at a mean time of 4 mo ostoperatively. Our study cohort reported no incidence of incontinence, which is consistent with the reports in other literature[ 30 , 31 ].…”
Section: Discussionsupporting
confidence: 93%